Investigating the influence of burden response on fragmentation at Sishen Mine - Moabelo, Matshidiso Tlou (University of the Witwatersrand, Johannesburg, 2024)
Sishen Mine is an iron ore mine based in the Northern Cape, 280 km north- west of Kimberley. The iron ore is extracted through means of drilling and blasting which utilises explosives to fragment the rock. This method of rock breakage requires blastholes to be assigned a delay timing. At Sishen Mine this is done through burden response. The mine has a set of timing guidelines that indicate the burden response range for each geological domain. The main focus of the study was on the waste and ore domains, which are blasted using the same burden response of between 12 ms/m to 18 ms/m. The aim of the study was to investigate the relationship between burden response and fragmentation and whether these timing guidelines for the ore domain result in the mine’s preferred fragmentation size of between 230 mm and 1400 mm where X80 is 600 mm. The study also aimed to investigate the impacts of fragmentation on loading rates and to measure the DMS ROM lump to fine ratio during and after determining the optimal burden response for the ore domain. The investigation was done from March 2022 to December 2023. It was carried out on 18 blocks in the North and South Mine pits. The research found that in the ore domain, fragmentation sizes increase with faster burden response. The fastest burden response used in the study was 14 ms/m and yielded X80 of 354.63 mm. Furthermore, Powergel Eco 35 explosive product resulted in coarser fragmentation in the ore domain compared to Innovex EGA. It was also found that loading rates reduced with increasing fragmentation size. The DMS ROM lump to fine ratio improved during the duration of the investigation. In 2021, the average lump to fine ratio was 77.74% which increased by 1.69% to 79.43% in 2022 and by 3.76% to 81.50% in 2023 indicating that a faster burden response improved lump to fine ratio. Ore blocks should be blasted with a burden response faster than 14 ms/m and waste blocks with a burden response range of 16 iv ms/m to 18 ms/m. However, more studies should be conducted on burden responses faster than 14 ms/m. Powergel Eco 35 should be used to charge ore blocks over Innovex EGA. Sishen Mine should consider including inter- hole delay timing on the timing guidelines.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment, School of Mining engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Burden response; fragmentation; inter-row delay timing; loading rates; lump to fine ratio; SDG-9: Industry, innovation and infrastructure